Manajemen Perubahan Kepala Madrasah dalam Penguatan Kompetensi Riset dan Inovasi Siswa pada Era Society 5.0 - Yeli Kurniati; Wilni Oktavia; Muhammad Fazis; Desi Purnama Sari (Indo-MathEdu Intellectuals Journal, 2026)
The research and innovation competencies of students in madrasas have not yet developed optimally, so a change strategy is needed that is able to build a culture of research and innovation in a sustainable manner. This study aims to analyze the change management of Islamic school principals in improving students' research and innovation competencies at MTsN 7 Lima Puluh Kota. The study used a qualitative approach with field research. Data were collected through observation, interviews, and documentation with informants consisting of Islamic school principals, supervising teachers, and students participating in the research and innovation program. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results show that Islamic school principals play a role as agents of change through strengthening a research culture, developing the Science Project and Technology Research Club (SPEKTRA) extracurricular program, teacher training, providing digital facilities, and collaborating with various parties. These strategies have been proven to support the improvement of students' research and innovation competencies, demonstrated through active involvement in research activities and achievements in national-level research competitions. These findings confirm that transformational leadership and change management are important factors in building a culture of innovation in madrasas.